Gastric Outlet Obstruction due to Peptic Ulcer Disease - Arif Sejati; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Gastric outlet obstruction is a rare complication of peptic ulcer disease, resulting from acute or chronic inflammatory changes. Patient may present asymptomatic or may have mild gastrointestinal symptoms. Some complications may include indirect systemic disorders such as water, acid-base, and electrolyte imbalance, which could be fatal. Acute management should include gastric decompression, correction of water and electrolytes abnormalities, as well as reduction of spasm and edema by using acid-supressants. After the patient has been stabilized, more definite measures should be taken such as endoscopic dilatation or surgery and treatment of peptic ulcer itself. Nowadays, endoscopic dilatation has been performed by using through-the-scope balloon dilating catheters. The diameter of balloon is usually increased gradually over several sessions. Long-term recurrence after endoscopic baloon dilatation has been reportedly low. Keywords: peptic ulcer, gastric outlet obstruction, endoscopic baloon dilatation